2011
DOI: 10.1039/c1cc10470e
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence PET (photo-induced electron transfer) sensors for water based on anthracene–boronic acid ester

Abstract: Anthracene-boronic acid ester as a new class of fluorescence PET sensors for detection of a trace amount of water in organic solvents has been designed and developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(63 citation statements)
references
References 25 publications
0
62
0
Order By: Relevance
“…These materials have found great utility in sensing humidity [1][2][3][4][5][6][7][8][9][10][11][12] and measuring the water contents of organic solvents. [13][14][15][16][17][18] Designs of hydrochromic humidity sensors can be based on conjugated organic molecules that undergo color changes associated with polarity changes caused by exposure to water. [ 1,2 ] Certain periodically ordered polymer fi lms, which have refl ectance wavelengths that the interchain distance in this polymer leads to partial distortion of the arrayed p-orbitals and an associated change in the wavelength maximum for visible light absorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These materials have found great utility in sensing humidity [1][2][3][4][5][6][7][8][9][10][11][12] and measuring the water contents of organic solvents. [13][14][15][16][17][18] Designs of hydrochromic humidity sensors can be based on conjugated organic molecules that undergo color changes associated with polarity changes caused by exposure to water. [ 1,2 ] Certain periodically ordered polymer fi lms, which have refl ectance wavelengths that the interchain distance in this polymer leads to partial distortion of the arrayed p-orbitals and an associated change in the wavelength maximum for visible light absorption.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Hydrochromic substances bearing amino-coupled fl uorophores also have been employed to determine the presence of water in organic solvents. [ 13,14 ] Sensors of this type emit only weak fl uorescence owing to the occurrence of facile quenching caused by photoinduced electron transfer (PET) from the amine moiety to the fl uorophore. However, in these systems blocking PET quenching by the formation of ammonium salt containing zwitterions when water is present in organic solvents results in the generation of strong fl uorescence.…”
mentioning
confidence: 99%
“…The results demonstrated that the fluorescence behavior of Mg-dpa-HC changed noticeably in the presence of a small amount of water. Therefore, Mg-dpa-HC shows potential for use as a highly sensitive sensor for the quantitative measurement of a trace amount of water in organic solvents 23 and real time imaging sensor for Mg 2+ in the cell membrane.…”
Section: +mentioning
confidence: 99%
“…7,8 Recently, numerous new types of boronic acid sensors have been fabricated to detect blood glucose concentrations, [9][10][11][12][13] ionic compounds, [14][15][16][17] traces of water in solvents, 18,19 hydrogen peroxide (H 2 O 2 ), [20][21][22] catecholamines, 23 as well as using boronic acids as biochemical tools for various applications, including tumor cell imaging, 24,25 enzyme inhibitors 26 and cell delivery systems. 27 Therefore, the boron-based uorescent sensor is still hot in today's research.…”
Section: 5mentioning
confidence: 99%